Partial cystectomy as a surgical option for colorectal cancer patients with pathological bladder invasion: an original retrospective study - Bing Lan; Rui Luo; Yang Li; Shijie Wang; Wei Jiang; Yun Zhong; Xuneng Zhang; Qingyang Zheng; Zichuan He; Bo Ma; Hui Wang; Keli Yang; et al. (Therapeutic Advances in Gastroenterology)
Background: Limited research exists on colorectal cancer (CRC) patients with bladder invasion, with survival outcomes post-cystectomy underexplored and a debate between partial and total cystectomy ongoing. Objective: The study aimed to evaluate the effect of pathological bladder invasion on the long-term tumour prognosis of patients with clinically diagnosed bladder invasion in CRC after cystectomy. Design: Retrospective, cohort study. Methods: Our study involving 105 CRC patients with bladder invasion who had partial or total cystectomy from 2012 to 2020 collected surgical and pathological data. Groups were divided by pathological bladder invasion presence and compared for 3-year overall survival (OS) and recurrence-free survival (RFS) rates. Multiphoton imaging assessed collagen features in some samples. Results: Pathological bladder invasion was confirmed in 50 patients (48%). Of 94 who had partial cystectomy, 41 were in the bladder invasion (+) group. The 3-year OS and RFS rates were 62.97% and 57.35% for the bladder invasion (+) group, and 77.16% and 58.68% for the bladder invasion (−) group, with no significant differences in recurrence rates between groups ( p  > 0.05). There are also no significant differences in 3-year local recurrence and intravesical recurrence rates between the two groups (18.62% vs 25.83%, 7.73% vs 11.82%, p  > 0.05). Distant metastasis was identified as an independent risk factor for OS and RFS by univariate and multivariate Cox regression analyses. Of the 24 samples that underwent multi-photon imaging, 142 collagen features extracted did not show statistical differences. Conclusion: Pathological bladder invasion impacts CRC patients’ post-cystectomy survival may be less than what clinical practice implies. Partial cystectomy in cases with pathological bladder invasion might offer similar survival rates to total cystectomy. Trial registration: ChiCTR2300077861.